The relevance of the first two eye fixations for recognition memory processes. Issue 6 (3rd July 2019) - Schwedes, Charlotte; Wentura, Dirk
ABSTRACT: Stimuli can be recognised based on information from only one or two eye fixations. With only one fixation, item recognition is typically above chance level and performance generally saturates by the second fixation. Thus, the first two eye fixations play an important role for recognition memory performance. However, little is known about the involved processes. Therefore, two experiments were conducted to investigate hypotheses regarding the role of the first two eye fixations for specific recognition memory processes, that is, familiarity and recollection. In addition, we looked in detail at the unique contributions of (a) longer input duration and (b) additional information provided by a second fixation for familiarity- and recollection-based recognition, using a gaze-contingent stimulus presentation technique. The experiments showed that recollection- but not familiarity-based recognition increased with two compared to only one fixation, and that the second fixation boosted recollection both due to longer availability of the input and additional stimulus information gathered.